2012
DOI: 10.2215/cjn.12601211
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Women with ESRD Requiring Hemodialysis

Abstract: SummaryBackground and objectives The few existing studies of sexual dysfunction in women on hemodialysis are limited by small sample size. This large, cross-sectional study evaluated the prevalence and correlates of female sexual dysfunction in advanced kidney disease.Design, setting, participants, & methods A total of 1472 women with ESRD undergoing hemodialysis were recruited to a multinational, cross-sectional study conducted within a collaborative dialysis network in Europe and South America. Sexual dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 44 publications
(48 reference statements)
2
49
1
4
Order By: Relevance
“…Sexual dysfunction also contributes to low pregnancy rates in women on dialysis. Among women on hemodialysis, 84% reported sexual dysfunction and only 35% of women reported being sexually active [6]. Depressive symptoms, medications, anemia and negative body image (potentially related to the presence of catheters and fistulas) contribute to low libido [7].…”
Section: Fertility and Esrdmentioning
confidence: 99%
“…Sexual dysfunction also contributes to low pregnancy rates in women on dialysis. Among women on hemodialysis, 84% reported sexual dysfunction and only 35% of women reported being sexually active [6]. Depressive symptoms, medications, anemia and negative body image (potentially related to the presence of catheters and fistulas) contribute to low libido [7].…”
Section: Fertility and Esrdmentioning
confidence: 99%
“…The association of increasing age with sexual dysfunction has been previously demonstrated in nonuremic subjects [23]. Strippoli's study showed that the prevalence of sexual dysfunction increased by 8% per 1-year increase [11]. Basok's study showed that low sexual function had relationship with existing diabetes [12].…”
Section: Discussionmentioning
confidence: 89%
“…In Seethala's study, 80% of women undergoing hemodialysis had a score of sexual function index less than 26.55 (7). More recently, in a large multicentric cross-sectional study, Strippoli et al [11] reported that 84% of women on maintenance hemodialysis had sexual dysfunction based on a cut-point of 26.55. The prevalence of sexual dysfunction in women who are of an age similar to that of our cohort and who have normal kidney function remains incompletely investigated.…”
Section: Discussionmentioning
confidence: 95%
“…However, all dialysis patients are associated with obvious severe somatic complications. If such conditions including sexual dysfunction 25,26) affect emotional disturbance, the SDS score may rather reflect the patient's true emotional condition. Note that the association between emotional disturbance assessed by the SDS test and mortality was extremely strong.…”
Section: Discussionmentioning
confidence: 99%